Vivienda social en Colombia - Torres Parra, Camilo Alberto; Saldeño Madero, Yelinca Nalena; Castiblanco-Prieto, Juan José; Villegas Flores, Noé (Editora Universitária da UNILA - EDUNILA, 2025)
The right to housing, although internationally recognized since 1948, has been widely neglected. United Nations data indicates that one in every 60 people on the planet has nowhere to live, and approximately one-fifth of the world’s population lives in precarious conditions. These alarming figures highlight the important role of construction professionals in addressing the needs of this vast portion of the global population—whether through the development of new housing or the improvement of existing living spaces. In this context, Edunila’s new collection, Habitar a América Latina (Inhabiting Latin America), rises to the urgency of bringing together discussions on housing and housing policies across the continent, where around 32% of the population lives in informal settlements. This reality is the result of a history of colonial domination, deeply tied to land concentration and slavery-based regimes aimed at sustaining economic elites. The book Social Housing in Colombia, which launches the collection, responds to this pressing issue by presenting the results of work carried out in popular neighborhoods of Bogotá. Without overlooking the armed conflict and its implications for Colombian cities, the authors acknowledge the region’s habitability problems and develop a methodology to assess the minimum quality of a home. This includes factors such as safety, legality, habitability, and structural design. Finally, it is important to highlight the cover illustration, created by Nicaraguan artist and architecture and urbanism faculty member at UNILA, Claudia Ochoa, who won first place in the 2023 contest organized by the publisher. This initiative helped establish Edunila as a space for creative and academic development within the institution. With a bold and thoughtful graphic design, we invite everyone to engage in the debate on the minimum conditions for habitability, as proposed by Camilo Torres, Yelinca Saldeño, Juan Castiblanco, and Noé Villegas.